Rebound Resilience Of Natural Rubber Composites Via Response Surface Methodology - Mohamad, Noraiham; Mazlan, Mazliah; Ab Maulod, Hairul Effendy; Abdul Razak, Jeefferie; Hamdan, Mohd Mef’at (Universiti Teknikal Malaysia Melaka, 2018)
A statistical model was developed in this study to describe rebound resilience of natural rubber composites which was prepared by using a Haake internal mixer. Response surface methodology (RSM) based on central composite centered design (CCD) was employed to statistically evaluate and optimize the conditions for maximum rebound resilience and study the significance and interaction of black filler and glycerol on rebound resilience yield.With the use of the developed quadratic model equation,a maximum rebound resilience 71° was obtained to be a black filler loading of 50 phr and glycerol loading of 7 %.